The potential therapeutic role of melatonin in organ fibrosis: a comprehensive review - Huang, Wei; Zheng, Juan; Wang, Ming; Du, Ling-Yao; Bai, Lang; Tang, Hong (Frontiers in Medicine, 2024)
Organ fibrosis is a pathological process characterized by the inability of normal tissue cells to regenerate sufficiently to meet the dynamic repair demands of chronic injury, resulting in excessive extracellular matrix deposition and ultimately leading to organ dysfunction. Despite the increasing depth of research in the field of organ fibrosis and a more comprehensive understanding of its pathogenesis, effective treatments for fibrosis-related diseases are still lacking. Melatonin, a neuroendocrine hormone synthesized by the pineal gland, plays a crucial role in regulating biological rhythms, sleep, and antioxidant defenses. Recent studies have shown that melatonin may have potential in inhibiting organ fibrosis, possibly due to its functions in anti-oxidative stress, anti-inflammation, remodeling the extracellular matrix (ECM), inhibiting epithelial-mesenchymal transition (EMT), and regulating apoptosis, thereby alleviating fibrosis. This review aims to explore the therapeutic potential of melatonin in fibrosis-related human diseases using findings from various in vivo and in vitro studies. These discoveries should provide important insights for the further development of new drugs to treat fibrosis.